Letter (copy) : Basque Children's Trust Limited - Tewson, Vincent
1942-07-23 038-0025-002 -2- it became necessary for administration purposes to merge the two Committees we did not actively pursue our association. There are several hundreds of basque children still in this country and I happen to be the Chairman of the Barnet Home which has been practically self-supporting since the early days. I know that the central fund is in very low waters and I am sure they would heartily welcome any support which your societies might give. Yours sincerely, Assistant Secretary 292/946/38/25(II)